Answer:
lkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkk
Step-by-step explanation:
Answer:
(x + 12)(x - 3)
Step-by-step explanation:
![{x}^{2} + 9x = 36 \\ {x}^{2} + 9x - 36 = 0 \\ {x}^{2} + 12x - 3x - 36 = 0 \\ x(x + 12) - 3(x + 12) = 0 \\ (x + 12)(x - 3) = 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%209x%20%3D%2036%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%209x%20-%2036%20%3D%200%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%2012x%20-%203x%20-%2036%20%3D%200%20%5C%5C%20x%28x%20%2B%2012%29%20-%203%28x%20%2B%2012%29%20%3D%200%20%5C%5C%20%28x%20%2B%2012%29%28x%20-%203%29%20%3D%200)
4 1/7 = (4*100) +(1/7 of 100)= (400+ 14.28)= 414.28
The answer is 414.28
The answer to this question is 25
Answer:
3+12i
Step-by-step explanation:
The difference of 5+3i and 2 + 1999 can be calculated as follows
= 5+3i - 2+9i
Collect the like terms
= 5-2+3i+9i
= 3+12i
Hence the difference of 5+3i and 2+9i is 3+12i